Pemberdayaan Kader SMART Stunting (Pencegahan dan Deteksi Pada Calon Pengantin, Ibu Hamil dan Balita) - Risqi Dewi Aisyah; Suparni Suparni; Edi Subowo (Journal of Community Development, 2025)
Stunting in young children is a significant global health issue, and it remains a serious concern in Indonesia with persistently high prevalence despite various interventions. This study highlights the importance of early detection and prevention of stunting through anthropometric measurements such as height and weight. Data from the 2022 Indonesian Nutritional Status Survey (SSGI) reveals that stunting rates in Central Java Province stand at 20.8%, with an increase in prevalence in Pekalongan District from 19.5% in 2021 to 23.5% in 2022. Stunting has serious consequences, including impaired brain development, reduced intelligence, and a higher risk of long-term health issues such as diabetes and cardiovascular diseases. This research focuses on training health cadres to improve early detection of stunting through the Community Partnership Program (PKM), aiming to enhance cadres' knowledge and skills in stunting detection and prevention. The results show an increase in knowledge among cadres by 11.63 points for stunting detection and prevention, and 21.67 points for nutrition-related topics. Additionally, 80% of cadres successfully performed anthropometric examinations. Collaboration between midwives and health cadres is expected to reduce stunting rates by improving monitoring and more effective interventions.